2001
DOI: 10.1097/00000478-200105000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus-8 Genes Are Expressed in Pulmonary Inflammatory Myofibroblastic Tumor (Inflammatory Pseudotumor)

Abstract: The presence of human herpesvirus-8 DNA sequences, as well as an overexpression of human interleukin-6 and human cyclin D1 in myofibroblastic cells of inflammatory myofibroblastic tumor (inflammatory pseudotumor), has recently been reported. We describe the pattern of human herpesvirus-8 gene expression in five cases of pulmonary inflammatory myofibroblastic tumor. Reverse transcriptase-polymerase chain reaction (RT-PCR), with several positive and negative controls, was performed to detect mRNA of 11 open read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(66 citation statements)
references
References 24 publications
0
63
0
3
Order By: Relevance
“…Whereas the demographic, clinical, and histological features in all cases were typical for inflammatory myofibroblastic tumor, no viral DNA or latent nuclear antigen was identified utilizing immunohistochemical or molecular studies. The observations reported by Gó mez-Román et al, 10 were based on five cases of ALK-negative pulmonary inflammatory myofibroblastic tumor and raised the question of whether the presence of virus is restricted to the lesions lacking ALK expression Absence of HHV-8 in IMT F Tavora et al and/or to lesions of the lung (Table 3). In a subsequent report, Yamamoto et al 22 addressed this issue utilizing 21 ALK-positive and ALK-negative tumors from multiple sites including lung.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas the demographic, clinical, and histological features in all cases were typical for inflammatory myofibroblastic tumor, no viral DNA or latent nuclear antigen was identified utilizing immunohistochemical or molecular studies. The observations reported by Gó mez-Román et al, 10 were based on five cases of ALK-negative pulmonary inflammatory myofibroblastic tumor and raised the question of whether the presence of virus is restricted to the lesions lacking ALK expression Absence of HHV-8 in IMT F Tavora et al and/or to lesions of the lung (Table 3). In a subsequent report, Yamamoto et al 22 addressed this issue utilizing 21 ALK-positive and ALK-negative tumors from multiple sites including lung.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Yamamoto et al study 22 had a limited number of pulmonary inflammatory myofibroblastic tumors, only three cases, and targeted only one ORF (ORF26). Similar to the study by Gó mez-Román et al, 10 we focused on pulmonary lesions and expanded the number of cases to 20, including 4 ALK-positive tumors; all 20 were negative for HHV-8. As we found no viral DNA, it was not surprising that all our cases were negative for latent nuclear antigen, corroborating the immunohistochemical findings on inflammatory myofibroblastic tumor from varying sites reported by Yamamoto et al 22 and pediatric cases reported by Mergan et al 23 Molecular identification of HHV-8 is known to produce both false-positive and false-negative results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The etiology and cellular origin of IMT remains unknown. Human herpes viruses 3 and 8, Eikenella corrodens, and Epstein-Barr virus have been proposed as possible infectious triggers of the IMT [3,4]. The most common sites of involvement are the lungs, mesentery, and omentum [2].…”
Section: Introductionmentioning
confidence: 99%